JTHS 2021
DOI: 10.7176/jths/57-01
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Tourism Investment in Emerging Destinations: Exploring Challenges and Opportunities: Evidences from Amhara Region, Ethiopia

Abstract: The current study examined challenges and opportunities of tourism investment through the lenses of Porter's five forces industry analysis. This study pursued an exploratory research design with qualitative approach. Academicians, travel agents, tour operators, hotel business owners and government tourism bureau experts were the main participants of the study. Findings of the current study unveil that inadequate infrastructure and mischief land use policy demise the growth of tourism investment in the study ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Research on tourism promotion in Ethiopia's Amhara region showed inadequate infrastructure and complicated land use regulations discourage tourism investment growth. However, a duty-free import policy for tourism investment, the availability of plentiful tourism resources, and backing from creditgranting institutions encourage tourism investment in the Amhara region (Kabete, 2021).…”
Section: Source: Author's Finding 2022mentioning
confidence: 99%
“…Research on tourism promotion in Ethiopia's Amhara region showed inadequate infrastructure and complicated land use regulations discourage tourism investment growth. However, a duty-free import policy for tourism investment, the availability of plentiful tourism resources, and backing from creditgranting institutions encourage tourism investment in the Amhara region (Kabete, 2021).…”
Section: Source: Author's Finding 2022mentioning
confidence: 99%